FSKKP inventory system using blockchain technology - Nurfazliyana, Arshad (2019)
FSKKP inventory system using Blockchain Technology is developed for Faculty of Computer Systems and Software Engineering. This proposed system will be used by the staff faculty as an admin and key in all the information of an inventory. The few problems occur when the limitation of space to keep the document because of increasing the device in FSKKP. The administrator difficult to trace an inventory when it lost or device was brake out. The problem also involves the lack of security appliance. The objective occurs to solve the problem in current system, which is to study the security level of Block chain technology work. Then, other objective is to develop FSKKP inventory system using Block chain technology. Other objective is to evaluate the Blockchain Technology occurs. Method used in developing this system is using System Development Life Cycle (SDLC) as a methodology because this method has flexible phase which the developer can make a change or any improvement to the system during the development phase. In addition, the system has to be done in a short period of time; within six months. This method is the best method to be used for the project. As a conclusion, this system is an advantage to the faculty that help to reduce the loosing data of an inventory.